DRAINAGE STUDY OF WAREHOUSE DEVELOPMENT PT. ANEKA INDUSTRI, SIDOARJO DISTRICT - Ismanto, Ikko Bagus; Nugroho, Laksono Djoko; Oetomo, Wateno (Transpublika Publisher, 2022)
The PT. Aneka Industri warehouse is located on a level with a slope of approximately 0-1%. Survey results from PT. Aneka Industri Warehouse in Tambaksawah Village, Waru District, Sidoarjo Regency, showed a height of -0.20m, slightly above the flood level of -0.10m. The area is likely to flood due to the overflow of Afvoer Bunung, which flows out from other areas (runoff water) during heavy rains. In addition, the storage area is a dense industrial area, and the chance of rainwater infiltration and loss is small. According to the analysis, the flood discharge of Afvoer Buntung during the 25-year return period is 193,305 m3/s. Meanwhile, the cross-sectional capacity of Afvoer Buntung is 25.707 m3/s, so the cross-section of Afvoer Buntung at the storage site of PT. Aneka Industri is flooded. It rains for t = 30 minutes, total volume = 297.57 m3.